The Sufistic Meaning Of The Calamity Verse: A Study of the Disaster Verses in the Tafsir of Faidl al-Rahman By Kiai Sholeh Darat Semarang 1894 AD (1312 H) - Abdul Wahab (AL QUDS : Jurnal Studi Alquran dan Hadis, 2026)
This study aims to analyze the sufistic meaning of disaster verses in Tafsir Faidl al-Rahman by Kiai Sholeh Darat and identify the characteristics of the sufistic patterns used in its interpretation. This research is a library-based study with a Sufistic approach. The primary source of research data is Tafsir Faidl al-Rahman. In contrast, secondary data is drawn from books, journal articles, and prior research on Kiai Sholeh Darat, Qur’an interpretation, and disaster theology. The results of the study show that Kiai Sholeh Darat interprets disasters not only as physical events that cause suffering but also as instruments of spiritual education and human moral transformation. Through the interpretation of QS. Al-Baqarah [2]: 11 and QS. In Al-Baqarah [2]: 155–156, disasters are understood as consequences of spiritual damage, tests of faith, and means of getting closer to Allah SWT. This research also finds that the Sufi orientation in Tafsir Faidl al-Rahman is more appropriately categorized as Sufi Isyari tafsir, which is characterized by an effort to explore the inner meaning of the verse without relinquishing its relationship with the zahir meaning of the Qur’anic text. These findings show that disaster theology from the perspective of Kiai Sholeh Darat is oriented towards spiritual awareness, moral improvement, and social transformation.